2020
DOI: 10.3389/fvets.2020.00246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fermented Corn–Soybean Meal on Gene Expression of Immunity in the Blood, Level of Secretory Immunoglobulin A, and Mucosa-Associated Bacterial Community in the Intestine of Grower–Finisher Pigs

Abstract: This study was conducted to determine the effect of a fermented corn-soybean meal [fermented feed (FF)] on the gene expression of immunity in the blood, the level of secretory immunoglobulin A (sIgA), and mucosa-associated bacterial community in the duodenum and colon of grower-finisher pigs. In this study, crossbred barrows (Duroc × Landrace × Large White) were randomly assigned to either an unfermented corn-soybean diet (Ctrl) (n = 6) or an FF diet (n = 6), and then the following were examined: the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…In line with this finding, a similar study observed that TLR3 and TLR8 were positively associated with the proportion of Rikenellaceae. 76 Little is known about the correlation between the different TLRs. Bösl et al investigated the coactivation of TLR2 and TLR8 in human primary monocytes and they found that TLR2 signal induced an inhibitory loop that reduced TLR8 signal intensity.…”
Section: Papermentioning
confidence: 99%
“…In line with this finding, a similar study observed that TLR3 and TLR8 were positively associated with the proportion of Rikenellaceae. 76 Little is known about the correlation between the different TLRs. Bösl et al investigated the coactivation of TLR2 and TLR8 in human primary monocytes and they found that TLR2 signal induced an inhibitory loop that reduced TLR8 signal intensity.…”
Section: Papermentioning
confidence: 99%
“…Lastly, the Lefse result of gut microbiota showed that Rikenellaceae , Muribaculum , Faecalibaculum , and Elisenbergiella in the LOP group had a significant difference compared with the other groups. Previous studies have found that Faecalicaculum, 63 Rikenellaceae , 64 Muribaculum , 65 Elisenbergiella 66 have a relationship with immunity. Hence, we speculate that LOP promote immune system maturation via increasing the abundance of Rikenellaceae , Muribaculum , Faecalibaculum , and Elisenbergiella.…”
Section: Discussionmentioning
confidence: 98%
“…However, these studies have not investigated the effects of fermented soybean meal on intestinal tight junctions and intestinal inflammation in weaned piglets. Additionally, although previous studies have demonstrated that fermented corn-soybean meal feed increases serum immunity, regulates mRNA abundance of antimicrobial peptides and Toll-like receptors and regulates gut microbiota in growerfinisher pigs [16,17], the effects of FMF in weaned piglets need further exploration. This study was conducted to investigate the effects of fermented corn-soybean meal mixed feed on growth performance, nutrient digestibility, intestinal barrier function, gut microbiota and short-chain fatty acids in weaned piglets.…”
Section: Analysis Of Substrates Before and After Fermentationmentioning
confidence: 99%
“…However, these studies have not investigated the effects of fermented soybean meal on intestinal tight junctions and intestinal inflammation in weaned piglets. Additionally, although previous studies have demonstrated that fermented corn–soybean meal feed increases serum immunity, regulates mRNA abundance of antimicrobial peptides and Toll-like receptors and regulates gut microbiota in grower-finisher pigs [ 16 , 17 ], the effects of FMF in weaned piglets need further exploration.…”
Section: Introductionmentioning
confidence: 99%